Stream discharge and water quality data for East Fork Poplar Creek beginning 2012. Issue 3 (23rd March 2021) - Brooks, Scott C.; Riscassi, Ami L.; Lowe, Kenneth A.
Abstract: This data note describes 15‐min discharge and in situ water quality data at two locations along East Fork Poplar Creek in east Tennessee, USA. Data records include temperature, gauge height, water surface elevation above mean sea level, and volumetric discharge. Water quality measurements include temperature, specific conductance, pH, dissolved oxygen (percent saturation and concentration), turbidity, and less extensive fDOM data at one site. The data records begin in 2012 at one site and 2015 at the second site; monitoring at both sites is ongoing (as of 2021). The goal of this data collection is to improve understanding of watershed functions, hydrologic dynamics, and material flux. The data will contribute to site conceptual and numerical models, exposure and risk evaluation, remediation selection and design, and performance monitoring. The data are publicly available and can be accessed via unique url or DOI. Abstract : This data note describes 15‐minute discharge and in‐situ water quality data at two locations along East Fork Poplar Creek in east Tennessee, USA. The goal of this data collection is to improve understanding of watershed functions, hydrologic dynamics, and material flux. The data will contribute to site conceptual and numerical models, exposure and risk evaluation, remediation selection and design, and performance monitoring. The publicly available data can be accessed via unique url or DOI.